Conceptual design of aluminium metal matrix composite brake rotor system - Maleque, Md. Abdul; Rahman, Md. Mustafizur; Hossain, Sayeed (Trans Tech Publications, Switzerland, 2011)
Composite materials have become a popular material substitution for automotive, sports, medical, aerospace and other engineering fields due to their light-weight, high strength and/or stiffness of fibres. In this paper, a conceptual design approach has been presented to develop aluminium metal matrix composite (AMC) automotive brake rotor system. A systematic and step by step approach of full design is shown for better understanding of the design concept of automotive brake rotor. The methodology of conceptual stage, computer aided design (CAD) and evaluation systems are discussed for illustrating and selecting the best concept. A total of six (6) concepts for both surface rejuvenates feature and ventilated cooling fins are explained. It was found that the Concept 6 for surface rejuvenates feature and Concept 1 for ventilated cooling fins are the best combination for aluminium metal matrix composite brake rotor application.